Practice and Associated Factors among Adult Residents towards Traditional Eye Medicine in Gondar City, North West Ethiopia - Minychil Bantihun Munaw; Natnael Lakachew Assefa; Dereje Hayilu Anbesse; Mebratu Mulusew Tegegne (Hindawi Limited, 2020)
Traditional medicines are commonly used in Africa. About 13.2-82.3% of the population use traditional eye medicine. The aim of this study was to assess practice and associated factors among adult residents towards traditional eye medicine in Gondar city, North West Ethiopia. Methods. A community-based cross-sectional study was conducted on 600 participants by using a pretested structured questionnaire. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 20 computer software. Association and strength between dependent and independent variables were determined using odds ratio with a 95% confidence interval. Results. A total of 600 respondents participated in the study with a 95 % response rate. From the total study participants, 73 (12.2%) (95% CI: 10-15%) had used traditional eye medicine in the past two years. Variables such as being unmarried (AOR = 0.48 (95% CI: 0.17-0.83)), being illiterate (AOR = 5.40 (95% CI: 5.3-12.3)), living in traditional healers available area (AOR = 2.84 (95% CI: 1.44-7.56)), poor access to modern eye care services (AOR = 2.11 (95% CI: 1.06-4.19)), and positive family history of traditional eye medicine use (AOR = 4.00 (95% CI: 1.84-8.67)) were significantly associated with traditional eye medicine practice. Conclusion. The proportion of traditional eye medicine practice was low in the past two years in Gondar city, Ethiopia, as compared to most African and Asian studies like south East Nigeria and Nepal, respectively. This may be due to the presence of tertiary eye care centers in the city that lets the residents prefer modern eye medicines over traditional eye medicines. Positive family history of traditional eye medicine use, being unmarried, being illiterate, poor access to modern eye care service, and availability of traditional healers had a significant association with the practice of traditional eye medicine. Community awareness about traditional eye medicine use is important to reduce the risk of complications even if the proportion is low.